Problems of official and unofficial political institutions in Iraq after 2003 - Mahdi Jaber Mahdi; Tara Omar Mohammed (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
Institutions and institutionalization are considered as essential pillars of the democratic political processes. This research has focused on studying the issues of, and the challenges that face, building formal and civic constitutional institutions in the most complicated stages in Iraq’s contemporary history, particularly after the dismantling of all the Iraqi state’s institutions by the occupying forces in 2003. The study examines the impediments and obstacles on the way of re-building public authority in Iraq represented by the formal institutions (legislative, executive, and judicial) as well as the civil institutions (political parties and civil society organizations), starting with the transitional period that includes the rule of the occupying power, the governing council, and the interim Iraqi government which ruled on the bases of Iraq’s Transitional Administrative Law, and ends with the Iraqi governments elected in the light of the country’s permanent constitution of 2005. The study concludes that the post-2003 Iraqi institutions in spite of all best changes, suffer from structural, constitutive, formative, legal, practical, instrumental and functional issues that have political, social, and economic dimensions. These issues have meant that state institutions have been weak and failed to meet the Iraqi citizens’ needs and demands.